Patients’ experiences of barriers and facilitators with continuous positive airway pressure therapy in obstructive sleep apnoea – a qualitative interview study - Karin Jeppesen; Anita Rabøl Good; Ilse Dall Dyrhaug; Marianne Bruun Johansen; Jette Primdahl (Archives of Public Health)
Abstract Background The prevalence of obstructive sleep apnoea ranges from 6 to 17% in the general adult population. Untreated obstructive sleep apnoea (OSA) is associated with cardiovascular disease, diabetes, traffic accidents, and decreased quality of life. Continuous positive airway pressure (CPAP) therapy is the gold standard for treating OSA. However, only approximately half of all treated patients succeed with this therapy. There is a lack of knowledge about the patient experience of CPAP treatment and the barriers and facilitators to successful CPAP treatment. The study aimed to explore how newly diagnosed patients with OSA experience receiving the diagnosis, their motivation for treatment, and essential factors for successful CPAP treatment. Methods A qualitative design using individual semi-structured interviews was applied. Patients with successful (n = 10) and unsuccessful (n = 9) treatment were interviewed. Qualitative Content Analysis inspired by Graneheim and Lundman was used. Results The analysis derived five themes: “Symptoms and thoughts about the diagnosis and CPAP treatment”, “Expectations and personal resources are important for success”, “The experience of problems and benefit from CPAP treatment”, “Social impact of CPAP treatment” and “Information and support from the sleep clinic.” Conclusions Newly diagnosed patients with obstructive sleep apnoea describe barriers to successful CPAP treatment as lack of support from their partner and problems with the equipment. Important facilitators are positive expectations, partner support, and noticeable treatment effects. Early follow-up support, a biopsychosocial approach, and relatives’ involvement in the sleep clinic consultations are needed to support patients toward successful CPAP treatment.